Giovanni Pirelli, intellectual and anti-colonialist activist (Altre Modernità, 2024)
The article analyzes the intellectual and political trajectory of Giovanni Pirelli (1918-1973) in light of his commitment as an anti-colonialist intellectual and militant. From his soutien to the Algerian liberation struggle in the late 1950s – in a Milan strongly involved in solidarity with the Algerian FLN – to the Third Worldist radicalization of the second half of the 1960s, Pirelli represented an important point of reference for the composite and heterogeneous archipelago of the so-called “New Left”. Thanks to the availability of his precious personal archive, in recent years the historiography on anticolonialism has finally been able to restore Pirelli’s commitment to its international dimension, reconstructing its crucial role in the dissemination of Frantz Fanon’s thought in Europe and its catalyzing function of (counter)information and support for anticolonial liberation movements.
Keywords: Giovanni Pirelli; anti-colonialism; Third Worldims; Algerian War of Independence; History of intellectuals; Frantz Fanon